Feed Utilisation of Chlorella Vulgaris Cultivated with Aquaculture Effluent - Takuya Sakomoto; Yugo Takabe; Takumi Uemura; Takanori Masuda; Yoshiko Hoshikawa (Journal of Water and Environment Technology, 2020)

(untitled)
The combination of aquaculture and microalgae cultivation with aquaculture effluent is a promising strategy, being economically and ecologically sustainable. This study explored the growth of Chlorella vulgaris and unintentionally cultivated microalgae with and without CO2 injection. The microalgae were cultivated with aquaculture effluent at the rearing temperature of coho salmon (18.5°C). In addition, we conducted batch and semi-continuous cultivations with unsterilized aquaculture effluent, demonstrating the dominance of C. vulgaris. Carbon was the limiting factor for microalgal growth in the effluent, and CO2 injection effectively enhanced the C. vulgaris growth. The highest percentage of C. vulgaris (over 99% of the total microalgal cells) was achieved by batch mode, by inoculating different amounts of C. vulgaris cells. This abundance resulted in the complete consumption of PO43− in the effluent. A dominant semi-continuous cultivation of C. vulgaris, containing 82 mg/L of suspended solids, was achieved in 23 days. However, the occurrence of zooplankton grazing resulted in a sharp decrease of C. vulgaris. The cultivated C. vulgaris presented a high total content of amino acids, and the amino acid composition suggested that they could be efficiently used as protein sources for coho salmon.